2013
DOI: 10.1080/15614263.2013.846982
|View full text |Cite
|
Sign up to set email alerts
|

Aligning policing and public health promotion: insights from the world of foot patrol

Abstract: Foot patrol work is rarely described in relation to public health, even though police routinely encounter health risk behaviors and environments. Through a qualitative study of foot patrol policing in violent ‘hotspots’ of Philadelphia, we explore some prospects and challenges associated with bridging security and public health considerations in law enforcement. Noting existing efforts to help advance police officer knowledge of, and attitudes toward health vulnerabilities, we incorporate perspectives from env… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(32 citation statements)
references
References 30 publications
0
32
0
Order By: Relevance
“…Despite these self-protective measures, it is evident from this study that the risk of law enforcement encounters is more likely when injecting drugs in semi-public spaces. Previous studies have demonstrated that law enforcement know these semi-public spaces as sites of drug use and activity, suggesting one explanation for this finding (Wood, Taylor, Groff, & Ratcliffe, 2015). …”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Despite these self-protective measures, it is evident from this study that the risk of law enforcement encounters is more likely when injecting drugs in semi-public spaces. Previous studies have demonstrated that law enforcement know these semi-public spaces as sites of drug use and activity, suggesting one explanation for this finding (Wood, Taylor, Groff, & Ratcliffe, 2015). …”
Section: Discussionmentioning
confidence: 90%
“…Attention to the nature of the social environment and its role in promoting or reducing the occurrence of deleterious outcomes such as overdose is an important intervention target. Having been injected by a “hit doctor” has previously been associated with receptive syringe sharing and HIV infection without the necessary harm reduction training (Wood et al, 2001; Wood et al, 2015). This result underscores the importance of tailored harm reduction interventions focused on nuances around the relationship and context of receiving an injection form a “hit doctor.” Our study further lends credence to the importance of promoting safe consumption spaces (SCSs), which are physical sites where PWID can bring previously-purchased illicit drugs to self-inject.…”
Section: Discussionmentioning
confidence: 99%
“…Police are not typically aware of the public health impact of their actions, despite the fact that they not only manage, but can also contribute to the health risk environment. Traditionally police role emphasize public safety (Wood et al, 2013) with FSW's more frequently perceived as criminals or informants, rather than victims. Few studies have qualitatively examined the nuanced nature of police-FSW interactions at the micro-level of daily policing (Simic & Rhodes, 2009; Milloy et al, 2011; Shannon, Kerr, Allinott, Chettier, Shoveller & Tyndall, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…This capability includes the routine sharing of information as well as issuing of public health alerts…in preparation for, and in response to, events or incidents of public health significance." Moreover, contemporary policing has recognized the importance of integrating public health information into policing strategies to further reduce crime, disorder, and calls for service while improving the quality of communities (Wood et al, 2015). Such strategies are rooted in the movement of harm-focused policing that seeks to facilitate public safety through a more expansive view of the role of police while "An emphasis on harm would provide a welcomed focus for intelligence-led policing" (Ratcliffe, 2015, pp.179).…”
Section: Private and Public Health Sectors As Fusion Center Partnersmentioning
confidence: 99%